فاعلية الذات بين المحتوى المعلوماتي والعمليات التنفيذية الميتامعرفية - دامخي, الأستاذة: ليلى (Sciences de l'Homme et de la Société, 2015)
يتناول الموضوع المطروح متغير فاعلية الذات، وتمركزها في العمليات الميتامعرفية من حيث هي مكون وجداني ميتامعرفي. وقد خلصنا من خلال تحليلنا للموضوع إلى توسط فاعلية الذات عمليات المعرفة الميتامعرفية، أو ما يسمى بـ "المحتوى المعلوماتي الميتامعرفي"، وعمليات الضبط التنفيذي للمهمة. وذلك لأن معتقدات الفاعلية الذاتية المرتفعة تتوقف على وعي بالذات المعرفية، ومتطلبات المهمة، والاستراتيجية التي تدعم الفاعلية الذاتية كحس ميتامعرفي وجداني. وفي المقابل فإن كفاءة التخطيط، والمراقبة، والتقويم الذاتيين كعمليات للضبط التنفيذي، وإن كان يحكمها حس معلوماتي ميتامعرفي، إلا أنها تتأثر بمعتقدات عن فاعلية الذات، والقدرات، أي بفاعلية ذاتية عالية لدى المتعلم. Abstract :                       The topic being investigated deals with the self-efficacy variable as a metacognitive affective component and its concentration in the metacognitive processes. From our analysis of the subject we reach to the fact that the self-efficacy mediates both the metacognitive processes - the so called metacognitive knowledge content- and the executive control processes of the task. This because the highly beliefs of the self-efficacy depends on self-efficacy awareness, the requirement of task and the strategy which supports self-efficacy as metacognitive emotional awareness. On the other hand, the planning competence, monitoring and self-evaluation as the processes of executive control despite being controlled by metacognitive knowledge yet are influenced by beliefs of self-efficacy and the abilities.  It means on a learner’s high self-efficacy.